HUBUNGAN PERILAKU 3M PLUS DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KOTA SEMARANG (STUDI DI KOTA SEMARANG WILAYAH ATAS) - Riza Nurul Husna; Nur Endah Wahyuningsih; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Indonesia is the second highest country of DHF’s case after Thailand. Some of the cities are endemic area. Semarang City is the one of endemic area that has been started from 1994 to 2015, which is illustrated by a rising trend line. Nowadays, DHF can caused by multifactorial. Behavioral factors is the biggest factors that influence someone’s health degree about 30-35%. Based on Depkes, DHF incidence of Semarang City (2015) mostly happen at the uptown region or hilly areas. By the case control design, using purposive sampling technique, this analytic observational study aims to analyze the relationship between the clean and health behavior through 3M Plus with the incidence of DHF in Semarang City. The sample are cases group, which has diagnosed with DHF and recorded in several hospitals in Semarang city, while the control groups were both done by age and sex matched. The results of 60 respondents from statistical analysis, chi square test, showed that there is no signification relation between 3M Plus behavior (p=1,000 OR=0,868) with the incidence of DHF in Semarang City. It was recommended for community to keep doing clean and health behavior, especially 3M Plus as government program, and giving more attention around the environment itself in order to always keep it clean and no potential place for Aedes aegypti breed.